2011
DOI: 10.32607/20758251-2011-3-2-13-21
|View full text |Cite
|
Sign up to set email alerts
|

Promoters with Cancer Cell-Specific Activity for Melanoma Gene Therapy

Abstract: Melanoma is one of the most aggressive tumors. It develops from pigment-forming cells (melanocytes) and results in a high number of lethal outcomes. The use of genetic constructs with the ability to specifically kill melanoma cells, but not normal cells, might increase the lifespan of patients, as well as improve their quality of life. One of the methods to achieve a selective impact for therapeutic genes on cancer cells is to utilize a transcriptional control mechanism using promoters that are specifically ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
3
0
1
Order By: Relevance
“…Репарационные системы, которые причастны к канцерогенезу: (1) система репарации 2-х нитевых разрывов ДНК; (2) система репарации неспраренных оснований (mismatch repair); (3) система эксцизионной репарации [18].80-90 % опухолей имеют дефекты в генах системы репарации [19,24,25,26,27,28,29]. Такой механизм способствует появлению клеточных клонов, содержащих все больше и больше вновь возникающих мутаций.…”
Section: таблица 1 биологическая функция протоонкогенов и антионкогеновunclassified
“…Репарационные системы, которые причастны к канцерогенезу: (1) система репарации 2-х нитевых разрывов ДНК; (2) система репарации неспраренных оснований (mismatch repair); (3) система эксцизионной репарации [18].80-90 % опухолей имеют дефекты в генах системы репарации [19,24,25,26,27,28,29]. Такой механизм способствует появлению клеточных клонов, содержащих все больше и больше вновь возникающих мутаций.…”
Section: таблица 1 биологическая функция протоонкогенов и антионкогеновunclassified
“…Those included promoters of oncogenes; promoters of genes involved in modulating the cell cycle; and promoters of genes known to enhance cell survival, angiogenesis, cancer progression, and metastasis. Additionally, promoters that are both tumor-specific and tissue-specific have been identified that can potentially target reporter gene expression in a particular tissue type, for example, genes involved in melanin biosynthesis (Pleshkan, Alekseenko, Zinovyeva, Vinogradova, & Sverdlov, 2011). …”
Section: Promotersmentioning
confidence: 99%
“…Yet some of these promoters can be used only in some specific cancer types and this fact limits their clinical applications. 1 Survivin is a member of the apoptosis inhibitors family (AIP) whose expression and activity increase in 60% to 70% of cancers but not in adult normal tissues. Recent studies suggest that overexpression of survivin is associated with resistance to chemotherapy, hormone therapy, and radiotherapy in many types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Yet some of these promoters can be used only in some specific cancer types and this fact limits their clinical applications. 1…”
Section: Introductionmentioning
confidence: 99%